The Implications of Parental Harvest Failure on Education Financing at Vocational High School (SMK) Diponegoro 2 Rawalo, Banyumas: Problems and Solutions - Khamid, Anwar; Hanif, Muh. (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the impact of crop failure on education financing management at SMK Diponegoro 2 Rawalo, where students’ families rely heavily on agriculture. Using a qualitative descriptive method, data were collected through interviews with school stakeholders and direct observation. Results show that crop failure reduces families’ ability to pay tuition, increases requests for financial aid, and forces schools to implement strategies such as fee waivers, payment rescheduling, and cross-subsidies. These conditions necessitate stronger internal financial management and enhanced communication with parents. The findings highlight the need for adaptive education financing policies in agriculturally dependent regions. Such policies are essential to maintaining education continuity amid economic instability caused by environmental factors.